Effect of Buteyko Breathing Exercise Combined with Postural Stability Exercises on Oxygen Saturation in Young Adult Smokers - Abd El-Hamied, Yasmeen Alaa; Abd El-Megied, Mohamed Ibrahim; Mohamed El-Batanouny, Mahmoud; Nashaat Halim, Mina; Aleem Fouda, Howida Abd El- (Journal of Neonatal Surgery, 2025)
Purpose: The purpose of the study was to examine the effect of Buteyko breathing exercise combined with postural stability exercises on oxygen saturation in young adult smokers. Methods: Forty male smokers were recruited from Nahda university. Their age ranged between 18-30 years. They were randomly allocated into two equally sized groups. Study Group: They participated in 6 weeks training with Buteyko breathing exercise combined with postural stability exercises (3 sessions per week) Control group: They weren’t exposed to any intervention. Both groups were assessed by using pulse oximeter to measure oxygen saturation (Spo2). Results: The mean ±SD values of the oxygen saturation levels among study group and control group at the conclusion of the study were 98.40±0.68 and 98.50±0.76 respectively. After-treatment oxygen saturation showed no appreciable statistical variation (P>0.05), according to the statistical analysis, between the study group and the control group P=0.664. The study group improved by 0.20%; the control group improved by 0.05%. Conclusion: It was found that there is minimal improvement but insignificant of Buteyko breathing exercise combined with postural stability on oxygen saturation in young adult smokers.